Las reducciones de capital por absorción de pérdidas y sus efectos en el costo computable de accionistas no domiciliados - León Puccio, Pablo Antonio (2019)
In our law system, non-domiciled individuals who decide to sell their shares in Peruvian companies must go through a certification procedure of invested capital presented to the Tax Administration. However, so far the Tax Administration has been adjusting the computable cost of shares owned by non-domiciled parties when Peruvian companies have made capital reductions to absorb losses by issuing such shares. In this article, the authors aim to determine whether capital reductions to absorb losses should imply a crease in the computable cost of shares of Peruvian companies that are disposed of by non-domiciled parties.